Biofilm Chitosan as Modern Dressing for Ulcers - Romanna Cintya Madeleine Simanjuntak; Wisye Riyoly; Fiane de Fretes; Agung Rimayanto Gintu (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Modern dressing techniques as open wound dressings are still effective and suitable for use, especially for people with open wounds such as ulcers, but they still have disadvantages, such as the high prices and need for other antibiotics to prevent inflammation. Previous studies reported an increase in the number of antibiotic resistance, which sparked the idea of producing new dressing materials that have strong antimicrobial and biocompatible properties. The material suitable for the idea of a wound dressing is chitosan biofilm because it has strong antibacterial properties and has a similar structure to the skin tissue. This study aims to produce chitosan biofilm using the deacetylation method using a strong base. The physicochemical characterization results of biofilms showed a deacetylation degree of 87.13 with a voltage of 1.15 ± 0.00 and a polycationic group of biofilms that appeared at a wavenumber of 2.1714 ± 0.0000 nm. From the measurement of the antibacterial power of chitosan biofilm against skin surface bacteria, the inhibition zone diameter was 18.93 ± 0.12; 19.50 ± 0.17; 20.20 ± 0.23; 20.13 ± 0.03 and 22.53 ± 0.09 against S. aureus, S. epidermidis, P. aeruginosa, E. colli, Bacillus sp. Overall, it can be concluded that biofilm chitosan has the opportunity to be applied as a dressing in wound care.